The Pandemic and the ’Techno-fix’ - Petit, Caroline; Longo, Giuseppe (Organisms. Journal of Biological Sciences, 2023)
The current pandemic was an announced possibility. Its potential causes were known: destroyed ecosystem niches, declining biological diversity, intensive farming, abuse of genetics, and biological manipulations. This paper deals with some aspects of the biological (and social) history of the ongoing COVID-19 pandemic but also with the history of previous epidemics, including the AIDS epidemics, which all have in common to be highly linked, enhanced or even the result of human activities. But now, the myth is setting in that an innovative technique for fast production of vaccines is the only and sufficient response to the crisis in the ecosystem and in health structures, of which this pandemic is a symptom. The reductionist and mechanistic approaches to the ecosystem and human biology are feeding the idea that the natural world may be fully manipulated and controlled (“the power to control Evolution” as in a recent book by a Nobel Award winner). This article calls for a critical thinking about the interfaces between the technosphere and the biosphere, their limits as well as for new frameworks for biology and medicine.